Optical Coherence Tomography of Pulmonary Arterial Walls in Humans and Pigs (Sus scrofa domesticus) - Brunner, Nathan W (Comp Med, 2015)
Pulmonary arterial hypertension (PAH) is a devastating disorder characterized by progressive elevation of the pulmonary pressures that, in the absence of therapy, results in chronic right-heart failure and premature death. The vascular pathology of PAH is characterized by progressive loss of small (diameter, less than 50 μm) peripheral pulmonary arteries along with abnormal medial thickening, neointimal formation, and intraluminal narrowing of the remaining pulmonary arteries. Vascular pathology correlates with disease severity, given that hemodynamic effects and disease outcomes are worse in patients with advanced compared with lower-grade lesions. Novel imaging tools are urgently needed that demonstrate the extent of vascular remodeling in PAH patients during diagnosis and treatment monitoring. Optical coherence tomography (OCT) is a catheter-based intravascular imaging technique used to obtain high-resolution 2D and 3D cross-sectional images of coronary arteries, thus revealing the extent of vascular wall pathology due to diseases such as atherosclerosis and in-stent restenosis; its utility as a diagnostic tool in the assessment of the pulmonary circulation is unknown. Here we show that OCT provides high-definition images that capture the morphology of pulmonary arterial walls in explanted human lungs and during pulmonary arterial catheterization of an adult pig. We conclude that OCT may facilitate the evaluation of patients with PAH by disclosing the degree of wall remodeling present in pulmonary vessels. Future studies are warranted to determine whether this information complements the hemodynamic and functional assessments routinely performed in PAH patients, facilitates treatment selection, and improves estimates of prognosis and outcome.